Study Of Postnatal Umbilical Cord Coiling Index and Its Association with Perinatal Outcome in a Tertiary Care Hospital - K B, Charumathi; Preethi B, Preethi B; Preethika A, Preethika A (Journal of Neonatal Surgery, 2025)
Background: The umbilical cord is often seen as just a connecting structure, but its unique pattern of coiling might hold valuable clues about a baby's health. Studies suggest that the number and tightness of coils—known as the Umbilical Coiling Index (UCI)—can affect how well the fetus tolerates labor and overall pregnancy outcomes. Objective: This study set out to examine how different patterns of umbilical cord coiling, measured after birth, relate to the baby’s health and the events around delivery. Methods: We conducted a three-month prospective observational study involving 92 women with single pregnancies between 37–40 weeks of gestation. After delivery, we measured the number of complete vascular coils in the cord and calculated the UCI. Based on this, cords were classified as hypocoiled, normocoiled, or hypercoiled. We then compared these groups against delivery mode, birth weight, Apgar scores, NICU admission, and other outcomes. Results: Most cords fell into the normocoiled category (54.35%), while 20.65% were hypocoiled and 25% hypercoiled. Babies with abnormal cord coiling were more likely to face complications like low Apgar scores, fetal distress, and NICU admission. Hypocoiling was especially linked to poor fetal growth and difficult labor, whereas hypercoiling had stronger ties with gestational diabetes and cesarean delivery. Conclusion: The pattern of umbilical cord coiling, often overlooked, may provide important insights into the baby’s well-being. Routinely evaluating UCI could help clinicians identify at-risk pregnancies and intervene early.